EFEKTIVITAS SUKU DINAS SUMBER DAYA AIR DALAM MENANGANI BANJIR DI KECAMATAN TANJUNG PRIOK - Bryan Swandana, Yosua; Pangestu, Angella Rosha; Wijayanto, Hendra (PROVIDER JURNAL ILMU PEMERINTAHAN, 2024)
This research aims to analyze the effectiveness of the Government, especially the North Jakarta City Administration Water Resources Department, in efforts to overcome flooding in Tanjung Priok District. The method in this research is qualitative with a descriptive approach. This research was carried out at the Water Resources Department, especially in Tanjung Priok District. Data collection was carried out by interviews and documentation studies, then analyzed descriptively narratively using the Miles & Hubberman model. The research results show that based on 7 (seven) indicators of effectiveness, the North Jakarta City Administration Water Resources Department has taken every step carefully and carefully. Targets and goals have been achieved well, where flood-prone areas have adequate equipment so that flooding does not have a more severe impact. In terms of timeliness indicators, the North Jakarta City Administration Water Resources Department carries out every treatment as responsively as possible after reports from flood detection monitoring. In terms of human resource indicators, North Jakarta Administrative City DSDA has quality and quantity human resources in their respective fields. So that flood management efforts, especially in the Tanjung Priok area, can be handled well. In terms of facilities and infrastructure indicators, the North Jakarta City Administration Water Resources Department provides various facilities that support flood management, such as stationary pumps, floating pumps and mobile truck pumps. The North Jakarta City Administration Water Resources Department carries out regular monitoring and evaluation to provide maximum service to the community. On budget indicators, the North Jakarta City Administration Water Resources Department carries out periodic budget planning. Budget management is also carried out transparently and accountability is maintained. In terms of communication and strategy indicators, the North Jakarta City Administration Water Resources Department coordinates with internal and external stakeholders as well as the community, so that flood management can be maximized when the community as key figures in the environment participates in maintaining environmental cleanliness.